2006
DOI: 10.4049/jimmunol.176.4.2249
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the Generation of a “Proteasome-Independent” MHC Class I-Restricted CD8 T Cell Epitope

Abstract: The proteasome is primarily responsible for the generation of MHC class I-restricted CTL epitopes. However, some epitopes, such as NP147–155 of the influenza nucleoprotein (NP), are presented efficiently in the presence of proteasome inhibitors. The pathways used to generate such apparently “proteasome-independent” epitopes remain poorly defined. We have examined the generation of NP147–155 and a second proteasome-dependent NP epitope, NP50–57, using cells adapted to growth in the presence of proteasome inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 59 publications
1
40
2
Order By: Relevance
“…This publication (27) reported results that seem to conflict with those presented here. Whereas in both reports LC enhanced presentation and AAF-cmk blocked it, we reached apparently different conclusions based mainly on results obtained with the TPPII-specific inhibitor butabindide and with gene silencing of the protease.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…This publication (27) reported results that seem to conflict with those presented here. Whereas in both reports LC enhanced presentation and AAF-cmk blocked it, we reached apparently different conclusions based mainly on results obtained with the TPPII-specific inhibitor butabindide and with gene silencing of the protease.…”
Section: Discussioncontrasting
confidence: 56%
“…Some differences in the experimental approach used in both reports may account for some of the discrepancies. First, Wherry et al (27) infected for longer periods and added the unstable butabindide less frequently than we did (as recommended (10)), which may leave a window of enzyme activity enough to allow for efficient presentation. Regarding gene silencing, Wherry et al (27) reported that only 50 -60% of cells were transfected, and thus, still many cells may present antigen, whereas we reached values of 95% leading to inhibition of antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations